The Impact Of Digital Sop Implementation On Transaction Process And Operational Efficiency: A Case Study Of Indomaret Stores In West Java - Adi Praptika Jaya; Taufik Sadikin (Pascasarjana STIE Amkop Makassar, 2026)
This study aims to analyze the effect of digital Standard Operating Procedure (SOP) implementation on transaction processes and operational efficiency at Indomaret stores in West Java. The research method employed an explanatory quantitative approach with a cross-sectional survey design involving 250 operational employee respondents from 45 stores. Data collection was conducted through closed questionnaires based on a 5-point Likert scale, with multiple regression analysis and Sobel mediation test. The results indicate that digital SOP has a positive and significant effect on transaction processes (β = 0.621; p < 0.001; R² = 0.386) and operational efficiency (β = 0.548; p < 0.001; R² = 0.312). Transaction process was proven to partially mediate the relationship between digital SOP and operational efficiency (Z = 4.12 > 1.96; R² = 0.497). These findings confirm that operational procedure digitalization is a determining factor in improving modern retail operational performance through transaction acceleration and resource optimization.Keywords: digital SOP, transaction process, operational efficiency, modern retail, Indomaret